The Role of Local Communities in Supporting Madrasah Management: A Comparative Study Between Indonesia and Thailand - Islahuddin, Islahuddin; rahman, arif; habiburrahman, Sayid (Jurnal Akuntabilitas Manajemen Pendidikan, 2024)
This research examines the role of local communities in supporting madrasah management in Indonesia and Thailand through a comparative approach. Madrasah, as an Islamic-based educational institution, has a strategic role in shaping the character and morals of students. In Indonesia, the integration of madrasahs in the national education system is supported by the government, while in Thailand, local communities play a major role in supporting the sustainability of madrasahs, especially in Muslim minority areas. This study uses a qualitative approach with a literature study method, which analyzes various secondary sources such as journal articles, research reports and policy documents. The results show that local community support includes financial, infrastructure and labor aspects. Differences in social, cultural and political contexts influence the pattern of local community contributions in both countries. In Indonesia, strong government support encourages more systematic management of madrasahs, while in Thailand, local communities have greater autonomy in madrasah management. Despite challenges such as limited resources and suboptimal management, both countries have opportunities to strengthen madrasahs through cross-country collaboration and inclusive education policy development. This research makes an important contribution to the development of Islamic education systems in Southeast Asia, especially in understanding the dynamics of synergy between local communities and faith-based educational institutions.